Wishful drinking [videorecording (DVD)] - Fisher, Carrie (HBO Home Entertainment, 2011)
As she demonstrates in this uproarious and often poignant performance, Carrie Fisher is not just an accomplished actress, screenwriter and best selling author. She's the offspring of showbiz royalty, daughter of celebrated actress Debbie Reynolds and crooner Eddie Fisher, whose very public affair with Elizabeth Taylor ended a storybook marriage. Revealed is the not-so-glittering side of being a celebrity, combining wry wit and raw facts to humanize Fisher's topsy-turvy life.